Enhance a Performance Productivity of Skills and Employee Services at Office Klambir Lima Village - Ikhah Malikhah; Suwarno Suwarno; Sepia Melati Putri (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The purpose of this study was to determine whether education, skills, and work ethics positively and significantly affect employee work productivity at staff employee office klambir Lima village. The data collection techniques in this study were conducted using a questionnaire with a list of claims to respondents of 50 respondents through the SPSS Version 17.0 assistance program. From the F test results obtained a Fcountof 12,734> Ftable2.81 and a significantly lower probability of 0.05 ie 0 .00 <0.05, then the regression model can be accepted that education, skills and work ethics simultaneously and significantly influence work productivity. From the partial variable test results, the educational value of 2.166> t table 1.67 with a significant 0.036 < 0.050, a significant positive and significant significance of Education against Employee Work Productivity. Skill Variable t-test value of 1.916 <t table 1.67 with a significant 0.62> 0.050, meaning that part does not require significant influence of Skills on Employee Work Productivity. Work Ethics Work ethics count 2,418> t table 1.67 with a significant 0.020 < 0.050, significantly influences the performance significantly and significantly from Work Ethics against Employee Work Productivity.